Design guide for stainless steel blast walls (FABIG technical note ;, 1999)
"Stainless steel blast walls made from profiled sheeting are commonly used on offshore process platforms where there is a risk of accidental gas explosions. They are usually required to survive the explosion in order to protect personnel and safety critical equipment and to prevent the spread of possible subsequent fire. They can also be used in onshore process plant and in other situations where protection from explosions is a requirement. This document gives guidance on the design of stainless steel blast walls made from profiled sheeting, including guidance on material behavior and selection, response to blast loading, design for longitudinal and transverse bending effects, evaluation of plastic deformation capacity and recommendations on construction details. The document specifically addresses walls constructed of panels with simple trapezoidal corrugations with or without longitudinal flange stiffeners manufactured from the grades of wrought stainless steel which are widely used in offshore structural applications."--Knovel.